High-gain DC-DC converter with advanced techniques: a review - Anitha Sagari Ravirala; T. Vijay Muni; T. Vinodita; K. Venkata Kishore; Ramoju Bheema Sankaram; Yuriy Yu Shvets (Institute of Advanced Engineering and Science, 2026)
This article provides an in-depth examination of recent advances in high-gain DC-DC converters, emphasizing soft-switching techniques and topological innovations that minimize voltage stress for renewable energy applications. High-gain DC-DC converters are crucial in photovoltaic and fuel-cell systems, where boosting low input voltages to higher levels must be achieved with high efficiency and compact design. Traditional boost converters fall short due to elevated switching stress, discontinuous input currents, and lower efficiency at high-gain levels. To address these limitations, this review categorizes and critically evaluates state-of-the-art converter topologies developed for high-gain operation. The main contributions of this review are as follows: i) A systematic classification of high-gain converter configurations with emphasis on their operational principles; ii) A detailed evaluation of soft-switching techniques, including zero voltage switching (ZVS) and zero current switching (ZCS), focusing on their roles in reducing switching losses and electromagnetic interference; iii) An analytical discussion on voltage stress mitigation methods and improved control strategies; and iv) An assessment of emerging trends in integrating advanced power electronics with renewable energy systems. These contributions collectively provide a comprehensive reference for researchers and engineers, supporting the development of next-generation high-performance DC-DC converters tailored for sustainable energy applications.